A numerical model for the simulation of double-diffusive natural convection in a triangular solar collector - Rahman, M.M.; Rahim, N.A.; Amin, N.; Saidur, Rahman (2011)
A numerical model is presented for the simulation of double-diffusive natural convection in a triangular solar collector. This design is encountered in greenhouse solar stills where vertical temperature and concentration gradients between the saline water and transparent cover induce flows in a confined space. This phenomenon plays an important function in the water distillation process and in the biological comfort. In this double-diffusion problem, the ratio Br of the relative magnitude thermal and compositional buoyancy and Rayleigh numbers are key parameters. Finite element technique is used to solve the governing equations. Numerical results are presented for the effect of the above-mentioned parameters on local heat and mass transfer rate. In addition, results for the average heat and mass transfer rate are offered and discussed for the mentioned parametric conditions. Some interesting results are found in this investigation.